Perilaku Struktur Gedung Bertingkat Tinggi dengan Variasi Penempatan Dinding Geser pada Rumah Susun ASN PUPR NTB - Hariadi, Rizal; Hariyadi, Hariyadi; Hidayati, Nurul (Jurnal Talenta Sipil, 2026)
The ASN PUPR Apartment Building in West Nusa Tenggara consists of 8 floors with a total height of 29,68m. All floors of this building utilize reinforced concrete structures, which makes them vulnerable to lateral forces, particularly those caused by earthquakes. Earthquakes pose a risk of structural damage; therefore, a strong structural system is required to withstand seismic forces in order to prevent collapse and structural failure. One such system is the optimal placement and configuration of shear walls to resist lateral forces. The research problem in this study is how to compare the effectiveness of three variations of shear walls in resisting lateral forces. The objective of this research is to analyze the floor displacement values in both the x and y directions and to determine the optimal location for shear wall placement in resisting lateral forces. This study employed a numerical simulation method based on structural modeling, using design drawings obtained from the project contractor. The floor displacement results for Variation 1 show a total displacement of 0,1611 mm in the x-direction and 0,1399 mm in the y-direction. Based on the analysis of the three structural models, it can be concluded that the placement of shear walls is more effective when positioned at the corner joints of the L-shaped building, as indicated by the floor displacement results in both the x and y directions.